Pharyngeal Dystonia Misdiagnosed as Cricopharyngeal Dysphagia Successfully Treated by Pharmacotherapy - Ho Eun Park; Myung Jun Shin; Je-Sang Lee; Yong Beom Shin (Annals of Rehabilitation Medicine, 2019)
A 43-year-old woman suffered from drooling and dysphagia after a stroke in the left posterior inferior cerebellar artery territory. Videofluoroscopic swallowing study showed compatible findings of cricopharyngeal dysphagia. Despite the injection of botulinum neurotoxin, no symptom improvement was achieved and pharyngeal dystonia was considered as the cause. Medications for dystonia dramatically helped with saliva control and resulted in a small improvement in the progression of food from the pharyngeal to esophageal phase. After adjusting the drug dose, the patient was able to perform social activities without drooling. Moreover, she could consume food orally; however, this was limited to small amounts of liquid, and the main method of nutrition support was via an orogastric tube. Therefore, we suggest that physicians should make a differential diagnosis of combined dystonia in patients complaining of dysphagia by esophageal manometry and electromyography.